Exploring the Success Factor Of Digital Marketing: A case study of Private Healthcare Organization in an Emerging Economy - Sidra Urooj Mallick (Institute of Business Management, 2023)
Abstract The purpose of this study is to assess the potential of social media platforms to build a successful marketing campaign for the private health-care industry. This will be accomplished by studying the current trends, audiences, and marketing tactics that are applied to these channels. In addition, the research will make a contribution to this understanding by investigating the efficacy of various types of marketing strategies that are used in the private health-care industry, such as influencer marketing, content marketing, and social media advertising, and how these strategies can be leveraged to create marketing strategies that are more effective. This research project will also focus on identifying any bottlenecks that could be hindering the utilisation of these channels and providing solutions to improve their effectiveness in the marketing mix. This will be done as part of the overall goal of improving the effectiveness of the marketing mix. At the end of the day, the purpose of this research is to develop an understanding of how social media channels can be utilised successfully as an important instrument in marketing for the health-care industry.